La diffusione del Cristianesimo nell'interno della Tripolitania attraverso i monumenti e sue sopravvivenze nella Tripolitania araba - Di Vita, Antonino (Quaderni di archeologia della Libya, 1967)
Keywords: Archéologie -- Djebel Nefousa; Christianisme -- Djebel Nefousa

Ancient Settlement in the Tripolitanian Gebel, II: The Berber Period - Oates, David (Papers of the British School at Rome, 1954)
Keywords: Archéologie -- Djebel Nefousa

Le antichità della Tripolitania - Bartoccini, Renato (Aegyptus, 1926)
Keywords: Archéologie -- Djebel Nefousa

Note al programma per l'explorazione archeologica della Tripolitania - Aurigemma, Salvatore (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Archéologie -- Djebel Nefousa

I Risultati scientifici e pratici delle campagne archeologiche coloniali - Romanelli, Pietro (Atti del Primo Congresso di Studi Coloniali, Firenze - 8-12 Aprile 1931 - IX, 1931)
Keywords: Archéologie -- Djebel Nefousa

The archaeology of Jebel Gharbi (Northwest Libya) and the Libyan sequence - Barich, Barbara E.; Conati Barbaro, Cecilia; Giraudi, Carlo (Interregional Contacts in the Later Prehistory of Northeastem Africa, 1996)
Keywords: Archéologie -- Djebel Nefousa

The Arabic Inscriptions on the Mosque of Abū Maʿrūf at Sharwas (Jebel Nefusa) - Lowick, Nicholas (Libyan Studies, 1973)
The medieval town of Sharwas – sometimes written Sharūs or Sarūs – figures in the writings of Ibn al-Warrāq (10th century A.D.), Ibn Hauqāl (10th century), al-Bakri (11th century), al-Idrīsi (12th century) and the anonymous author of the Kitāb al-Istibṣār (12th century). All are agreed that it was an important place, the chief settlement (umm qura) of the Jebel Nefusa. It had no congregational mosque (jāmic), but was one of the two towns in the Jebel provided with a minbār or pulpit. The name Abū Macrūf, as applied to the mosque and the surrounding ruins, does not appear in the medieval sources but certainly goes back many centuries in oral tradition. It refers to Abū Macrūf Wiyār ibn Jawād, a famous religious figure of the later 9th century who lived a short distance to the south-east of Sharwas and who was present at the battle of Mānū in A.H. 283/A.D. 896 - 7.A preliminary note on Sharwas and its mosque has already appeared in the Second Annual Report of this Society (pp. 10 - 11). There are no less than sixteen monumental inscriptions carved on separate blocks of stone outside and inside the Mosque. Most important for the dating of the structure is the two line inscription (no. 1, pl. VIa) in the tympanum of the west doorway. This is in the ornamented variety of Kufic usually referred to as ‘floriated’ The style is decidedly ‘provincial’ and does little credit to the engraver. Nevertheless it is possible to discern, in such features as the trifoliate ending to the dāl of waḥdahu in the first line, points of resemblance to the later of the two monumental inscriptions from Ajdābiyah published in the Society's Third Annual Report (p. 5, Pl. VIIIb). This is dated A.H. 351/A.D. 962. If it is true, as there suggested, that the floriated style was introduced into Libya between c. 922 and 962 A.D., then the inscription over the doorway at Sharwas is unlikely to be earlier than the second half of the the 10th century, allowing for the town's somewhat isolated position in the Tripolitanian hinterland. It may, indeed, be as late as the 12th century, if the present Mosque postdates the destruction of Sharwas, c. 1100.
Keywords: Architecture -- Djebel Nefousa; Archéologie -- Djebel Nefousa

Tripolitania in transition: late Roman to Islamic settlement: with a catalogue of sites - Sjöström, Isabella (Worldwide archaeology series, 1993)
Pp. 141-182: site catalogue of the Jabal Nafūsa
Keywords: Archéologie -- Djebel Nefousa

Hadd Hajar, a clausura in the Tripolitanian Gebel Garian south of Asabaa - Brogan, Olwen (Libyan Studies, 1980)
In the Gebel Garian, about 20 kilometres south of Asabaa, the map-makers of 1964 indicated an ancient wall (Fig. 1) called Hadd Hajar (i.e. wall of stone) running south-west for six kilometres from Ras al Tays al Abyad (858 m; the Hill of the White Goat) on which stood a watch tower, to Ras al Said (764 m). The country crossed by Hadd Hajar is about 690-730 m above sea-level with a gently-undulating surface constituting a fairly open and level valley. The hills are covered with esparto-grass. On the west the Wadi Wamis winds among closely-set hills while, in the north-east, the wall is carried for a further three quarters of a kilometre across a narrow valley from Ras al Tays al Abyad to another hill Ras al Saqifah. An old track comes southwards down this valley flanked on the east side by a barrier of hills over 800 m high. Where the track crosses the wall there is a Roman building (Gasr al Saqifah) with traces of an archway for people and flocks to pass through. Two kilometres to the south is an old cistern (Majin Saqifah) presumably Roman. Beyond, the track continues about 25 kilometres to a large well, Bir al Shaqaykah (Sceghega), after which it is another 28 kilometres south-eastwards to Mizdah on the Wadi Sofeggin.
Keywords: Archéologie -- Djebel Nefousa

Chasseurs et pasteurs du Messak Settafet (Fezzan - Libye) - Van Albada, Axel; Van Albada, Anne-Michelle (Préhistoire Anthropologie Méditerranéennes, 1992)
Keywords: Archéologie -- Djebel Nefousa

Islamic archaeology in Libya, 1969-1989 - King, G.R.D. (Libyan Studies, 1989)
Keywords: Archéologie -- Djebel Nefousa

Pottery and the History of Roman Tripolitania: Evidence from Sabratha and the UNESCO Libyan Valleys Survey - Dore, J.N. (Libyan Studies, 1988)
This article considers some of the ceramic evidence from Sabratha (the excavations of 1948-1951) and from the pre-desert to the south-east of the Gebel Gharian (the area of the UNESCO Libyan Valleys Survey). The association of fineware with different classes of site in the Valleys area is used to construct a chronological framework for settlement within the area. Some of the commoner coarseware types from Sabratha are illus- trated and discussed.
Keywords: Archéologie -- Djebel Nefousa

Amphora Production in the Tipolitanian Gebel - Arthur, P. (Libyan Studies, 1982)
Keywords: Archéologie -- Djebel Nefousa

Stazione litica all'aperto nei pressi di Garian - Fabbri, M.; Winorath-Scott, A. (Libya Antiqua, 1965)
Keywords: Archéologie -- Djebel Nefousa

The Tripolitanian Gebel: Settlement of the Roman Period around Gasr Ed-Dauun - Oates, David (Papers of the British School at Rome, 1953)
Keywords: Archéologie -- Djebel Nefousa

Di alcune iscrizioni in carateri latini e in lingua sconosciuta, trovate in Tripolitania - Beguinot, Francesco (Rivista degli studi orientali, 1949)
Keywords: Archéologie -- Djebel Nefousa

The Christian Antiquities of Tripolitania - Perkins, John Bryan Ward; Goodchild, Richard G. (Archaeologia or miscellaneous tracts relating to antiquity, 1953)
Keywords: Archéologie -- Djebel Nefousa; Christianisme -- Djebel Nefousa

La diffusione del cristianesimo nell'interno della Tripolitania, attraverso i monumenti, e sue sopravvivenze nella Tripolitania araba - Di Vita, Antonino (Corso di Cultura sull'Arte Ravennate e Bizantina, 1966)
Keywords: Archéologie -- Djebel Nefousa; Christianisme -- Djebel Nefousa

Le Djebel Gharian. Les Troglodytes de La Tripolitaine - Slousch, Nahum (Revue du monde musulman, 1908)
Keywords: Archéologie -- Djebel Nefousa

Gasr el-Gezira, a Shrine in the Gebel Nefusa of Tripolitania - Brogan, Olwen; Oates, David (Papers of the British School at Rome, 1953)
Gasr el-Gezira stands on high ground about one kilometre south of the edge of the escarpment overlooking Wadi el-Matmùra where it debouches on to the Gefara, the coastal plain of Tripolitania, and about four kilometres due north of kilometre-stone 166 on the Jefren—Giado road. The escarpment in the neighbourhood is over 400 metres high, and the building stands at a height of 745 metres above sea-level, on the watershed between the wadis running down to the Gefara and those feeding the affluents of the Upper Sofeggin system to the south. The building is surrounded by scattered troglodyte dwellings and sparse olive groves, interspersed with fig gardens and more open land used for cereal cultivation. The remains of a Roman village lie some three hundred metres to the south-east, and the whole complex marks the north-eastern extremity of an area of Roman olive cultivation, roughly coinciding with the district known as ez-Zintan, and probably to be assigned to the period between the first and the fourth centuries a.d .
Keywords: Archéologie -- Djebel Nefousa

Bir et-Uaar Mausoleum (Al-Urban, Djebel Garian) - Abdussaid, Abdulhamid (Libya Antiqua, 1998)
Keywords: Archéologie -- Djebel Nefousa

The Suq al Jum'ah Palaeowadi, an Example of a Plio-Quaternary Palaeo-valley from the Jabal Nafusah, Northwest Libya - Ghellali, S. M.; Anketell, J. M. (Libyan Studies, 1991)
Study of borehole data in the foothill region of the Jabal Nafusah shows that the Suq al Jum'ah palaeowadi, which cuts the jabal east of Gharyan, comprised a major drainage channel which extended in the subsurface far out from the jabal into the southern part of the Jifarah Plain. The channel is filled with sands and gravels. Basalt lava flows, channelled along the valley in outcrop for 36 km, extend for a further 48 km in the subsurface. The palaeowadi was possibly initiated in the Pliocene and appears to have been completely filled and abandoned by the end of the Pleistocene. During Holocene rejuvenation of the drainage system, the Wadi al Majanin developed as the major wadi in the region. It did not, however, excavate the palaeowadi but instead followed a different but roughly parallel northward trend.
Keywords: Archéologie -- Djebel Nefousa

Vestigia di colonie agricole romane: Gebel Nefusa - Corò, Francesco (Collezione di Opera e di Monografie, 1929)
Keywords: Archéologie -- Djebel Nefousa

Geoarchaeology of the Jebel Gharbi Region : outline of the research - Barich, Barbara E.; Giraudi, Carlo; Conati Barbaro, Cecilia; Capezza, Cecilia (Libya Antiqua, 1995)
Keywords: Archéologie -- Djebel Nefousa

Scavi italiani al Gebel Barkal - Donadoni, S.; Bosticco, S. (Meroitica, 1982)
Keywords: Archéologie -- Djebel Nefousa

The Limes Tripolitanus: a Roman Road in North Africa - Hammond, Norman (Journal of the British Archaeological Association, 1967)
Keywords: Archéologie -- Djebel Nefousa